Stable, Efficient, and All-Solution-Processed Quantum Dot Light-Emitting Diodes with Double-Sided Metal Oxide Nanoparticle Charge Transport Layers - Yang, Xuyong (2016)
An efficient and stable quantum dot light-emitting diode (QLED) with double-sided metal oxide (MO) nanoparticle (NP) charge transport layers is fabricated by utilizing the solution-processed tungsten oxide (WO3) and zinc oxide (ZnO) NPs as the hole and electron transport layers, respectively. Except for the electrodes, all other layers are deposited by a simple spin-coating method. The resulting MO NP-based QLEDs show excellent device performance, with a peak luminance of 21300 cdm-2 at the emission wavelength of 516 nm, a maximal current efficiency of 4.4 cdA-1 and a low turn-on voltage of 3 V. More importantly, with the efficient design of the device architecture, these devices exhibit a significant improvement in device stability and the operational lifetime of 95 h measured at room temperature can be almost 20-fold longer than that of the standard device.